Does the urban low-carbon transition promote the residents’ health consumption? - Pian Chen; Yanchi Chen (PLoS ONE, 2025)
This work employs a fixed-effects model to analyze the influence of urban low-carbon transition on residents’ health consumption, utilizing data from the China General Social Survey (CGSS) for the years 2018 and 2021. The model estimation value is 0.1349, significant at the 5% confidence range, demonstrating that urban low-carbon transition enhances residents’ health consumption. This result successfully underwent both the robustness test and the endogeneity test. The mechanism test reveals that urban low-carbon transition influences residents’ health consumption through two pathways: increasing health awareness and improving the level of habitat environment. The heterogeneity studies indicate that the impact of the urban low-carbon transition on residents’ health consumption varies according to income levels, gender, and urban development stages. Higher-income people, female residents, and those in locations with advanced urban development significantly contribute to this influence. The study ultimately presents pertinent policy proposals aimed at enhancing the urban low-carbon transition, increasing the residents’ understanding of health consumption, improving the level of habitat environment, and paying attention to coordinated and healthy development.